(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The article discusses the issues of import substitution in the Voronezh region, as well as measures provided by the state to support investment, innovation, scientific and technical activities of industrial production in the region. The allocated sums directed by the Governor of the Voronezh region for the development of industry are disclosed. The positive result of state support largely explains the competitiveness of production in the Voronezh region. It is concluded that the industrial enterprises of the Voronezh region are dynamically working under the import substitution program, which helps to cope with the problems that have arisen in our country - with the sanctions imposed against Russia.